2015
DOI: 10.3386/w21439
|View full text |Cite
|
Sign up to set email alerts
|

Who's Getting Globalized? The Size and Implications of Intra-national Trade Costs

Abstract: How large are the intra-national trade costs that separate consumers in remote locations of developing countries from global markets? What do those barriers imply for the intra-national incidence of the gains from falling international trade barriers? We develop a new methodology for answering these questions and apply it to newly collected CPI micro-data from Ethiopia and Nigeria (as well as to the US). In order to overcome three well-known challenges that arise when using price gaps to estimate trade costs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(51 citation statements)
references
References 41 publications
2
47
0
2
Order By: Relevance
“…Trade costs are very high in much of the developing world. In Ethiopia and Nigeria for instance, trade costs are four to five times larger than in the United States (Atkin & Donaldson, 2015). A significant portion of trade costs in developing countries, especially in African countries, is actually non-physical (Raballand, Macchi, & Petracco, 2010), reflecting costs and delays associated with border crossing, price mark-ups of non-competitive transport firms, and bribes.…”
Section: Tradementioning
confidence: 99%
“…Trade costs are very high in much of the developing world. In Ethiopia and Nigeria for instance, trade costs are four to five times larger than in the United States (Atkin & Donaldson, 2015). A significant portion of trade costs in developing countries, especially in African countries, is actually non-physical (Raballand, Macchi, & Petracco, 2010), reflecting costs and delays associated with border crossing, price mark-ups of non-competitive transport firms, and bribes.…”
Section: Tradementioning
confidence: 99%
“…Weyl and Fabinger (2013) presents a unifying framework for incidence with imperfect competition. This framework has been fruitfully utilized in the context of developing countries by Atkin and Donaldson (2015). Analogous to our approach, they use the BulowPfleiderer (1983) specification of demand to derive a constant pass-through rate that depends only on market concentration and demand curvature.…”
Section: Related Literaturementioning
confidence: 99%
“…We show this in the context of a model of symmetric Cournot competition with given concentration at each 1 layer. As in the recent work of Atkin and Donaldson (2015), a Bulow-Pfleiderer (1983) specification of downstream consumer demand generates explicit linear recursive expressions for prices at each layer in the absence of any credit rationing.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence by Atkin and Donaldson (2015) suggested that the answer to this question may be country-specific. They showed that in Ethiopia and Nigeria, national trade costs may be 4-5 times larger than in the US, implying that more priority should be given to investment in national infrastructure in Ethiopia and Nigeria than in the US.…”
Section: National Versus International Infrastructurementioning
confidence: 99%